The Sources of Business Cycles in a Low Income Country - Houssa, Romain (IMF Working Papers; Working Paper ;, 2015)
We examine the role of global and domestic shocks in driving macroeconomic fluctuations for Ghana. We are able to study the impact of exogenous shocks including productivity, credit supply, and commodity price shocks. We identify the shocks with a combination of sign and recursive restrictions within Bayesian VAR models. As a benchmark we provide results for South Africa to document the difference between two economies with similar structures but different levels of development. We find that global shocks play a more dominant role in South Africa than in Ghana. These shocks operate through three channels: trade, credit and commodity prices.